Clozapine Prescribing in the General Hospitals - Hanna Tee; Namrata Soni; Kara Hosegood; Dhaveena Rajathevan (BJPsych Open, 2025)
Aims: Clozapine is an effective treatment for adults with schizophrenia, who have not responded to two other antipsychotic medications. However, there are challenges prescribing when patients who take clozapine in the community are admitted to a General Hospital for physical health reasons. These challenges can include physical health co-morbidities, medication interactions, blood dyscrasias, changes in smoking status and bowel movements, infection, missed or incorrect doses of clozapine prescribed, and clozapine toxicity.